Ectopic Pregnancy and its Risk Factors: A Case Control Study in Nepalese Women - Bhandari, G.; Yadav, K.K.; Shah, R. (Journal of BP Koirala Institute of Health Sciences, 2018)
Introduction: Ectopic pregnancy is a significant cause of maternal mortality and morbidity during the first trimester. The major risk factors for ectopic pregnancy include prior tubal infections, previous ectopic pregnancy, previous abortions, use of intrauterine contraceptive devices, contraception failure, tubal surgeries, infertility and use of artificial reproductive pregnancies. This study was carried out to evaluate the effect of different risk factors in the causation of ectopic pregnancies among women in the Nepalese setting. Materials and methods: This was a case-control study conducted at Kathmandu Medical College comparing 39 cases of ectopic pregnancies with 39 controls consisting of intra-uterine pregnancies. The suspected cases were confirmed through clinical examination, trans-abdominal or trans-vaginal ultrasonography and serum β-hCG levels with further confirmation obtained after laparotomy / laparoscopy among cases who underwent surgery. The two study groups matched with age, gravidity and contraceptive uses were studied. History of previous abortions, previous ectopics and past abdomino-pelvic surgeries were also studied. Results: There was statistically significant difference in the incidence of contraceptive failure among the two groups (p-value= 0.032) with women with such history having a relative risk of 1.667 with odds ratio of 3.400. The risk posed by previous abortions and previous ectopics wasn’t found significant (RR= 1.000 and 2.053 respectively). The history of past abdomino-pelvic surgeries also showed significant role in causation of ectopics (RR= 1.094). Conclusion: Among different risk factors studied, the contraception usage was the most significant risk factors. Oral contraceptive pills was the most identified among the contraception used in cases of ectopic pregnancy.